Ammonia assimilation by Aspergillus nidulans: [15N]ammonia study - Kusnan, Misri; Klug, Klaus; Fock, Heinrich P. (Society for General Microbiology, 1989)
15N kinetic labelling studies were done on liquid cultures of wild-type Aspergillus nidulans. The labelling pattern of major amino acids under 'steady state' conditions suggests that glutamate and glutamine-amide are the early products of ammonia assimilation in A. nidulans. In the presence of phosphinothricin, an inhibitor or glutamine synthetase, 15N labelling of glutamate, alanine and aspartate was maintained whereas the labelling of glutamine was low. This pattern of labelling is consistent with ammonia assimilation into glutamate via the glutamate dehydrogenase pathway. In the presence of azaserine, an inhibitor of glutamate synthase, glutamate was initially more highly labelled than any other amino acid, whereas its concentration declined. Isotope also accumulated in glutamine. Observations with these two inhibitors suggest that ammonia assimilation can occur concurrently via the glutamine synthetase/glutamate synthase and the glutamate dehydrogenase pathways in low-ammonia-grown A. nidulans. From a simple model it was estimated that about half of the glutamate was synthesized via the glutamate dehydrogenase pathway; the other half was formed from glutamine via the glutamate synthase pathway. The transfer coefficients of nine other amino acids were also determined.